2019
DOI: 10.1080/10428194.2018.1535113
|View full text |Cite
|
Sign up to set email alerts
|

The potential health gain and cost savings of improving adherence in chronic myeloid leukemia

Abstract: Healthcare costs are rising due to an increase in chronic diseases, including chronic myeloid leukemia (CML) due to improved survival. In CML care, patient adherence and physician adherence are key elements. We assessed the potential health gain and cost savings when both are improved, using a decision analytic model that integrated various sources of evidence. The current situation was compared to a theoretical situation in which either patient or physician adherence is improved, in terms of costs and quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…To date, only 2 of the assessments were published. 19,20 Due to the confidentiality of the information, we were limited in the amount of information we could provide on the assessments. Confidentiality is often an issue in early HTA, when commercial viability is assessed.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 2 of the assessments were published. 19,20 Due to the confidentiality of the information, we were limited in the amount of information we could provide on the assessments. Confidentiality is often an issue in early HTA, when commercial viability is assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In CML care, treatment decisions increasingly incorporate patient and physician preferences regarding multiple aspects of quality of life, practicality, and cost-effectiveness [ 21 ]. Previous studies in CML have found poor to moderate agreement between physician and patient reports of symptom severity, health status, and pain after TKI discontinuation [ 13 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing adherence could save health care costs. A Dutch report assessed the potential value of improving both patients’ adherence to TKIs and physicians’ adherence to guidelines [ 63 ]. For each yearly cohort of newly diagnosed patients with CML (160 patients) over a period of 25 years, a cost reduction of approximately US $3.1 million (€2.8 million) and US $1.3 million (€1.2 million) would be possible by improving the patients’ adherence and physicians’ adherence, respectively, to 100%.…”
Section: Discussionmentioning
confidence: 99%